Dipeptidyl peptidase-4 inhibitors and the ischemic heart: Additional benefits beyond glycemic control - Chattipakorn N. (2017)
© 2015 Elsevier Ireland Ltd. All rights reserved. Obese-insulin resistance and type 2 diabetes mellitus (T2DM) have become global health problems, and they are both associated with a higher risk of ischemic heart disease. Although reperfusion therapy is the treatment to increase blood supply to the ischemic myocardium, this intervention potentially causes cardiac tissue damage and instigates arrhythmias, processes known as reperfusion injury. Dipeptidyl peptidase 4 (DPP-4) inhibitors are glycemic control drugs commonly used in T2DM patients. Growing evidence from basic and clinical studies demonstrates that a DPP-4 inhibitor could exert cardioprotection and improve left ventricular function by reducing oxidative stress, apoptosis, and increasing reperfusion injury salvage kinase (RISK) activity. However, recent reports also showed potentially adverse cardiac events due to the use of a DPP-4 inhibitor. To investigate this disparity, future large clinical trials are essential in verifying whether DPP-4 inhibitors are beneficial beyond their glycemic control particularly for the ischemic heart in obese-insulin resistant subjects and T2DM patients.